Self-Assessment to Assist Students in Writing Descriptive Texts - Miqawati, Alfi Hidayatu (Politeknik Negeri Jember, 2019)
Most students find writing hard since it requires a complex process and strategies. They should cover not only all the dimensions of writing, such as content, organization of ideas, language use, mechanics, but also other important aspects such as, how they convey their ideas and do the editing process. They usually miss these aspects from the very beginning, the pre-writing process.Â Therefore, the teacher should give an effective strategy for the students to write. It is critical to provide them strategies so that they can assist themselves in their writing process. Self-assessment is one of the strategies that encourages students to be able to think about their purpose in writing and to reflect on what and how much they are learning. This article discusses the benefits and practical implementation of self-assessment to assist the studentsâ€™ writing process. Teachers should implement it frequently because it needs a process to train the students to develop their self-efficacy.